2003
DOI: 10.1074/jbc.m303411200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase Maturation and Oligomerization in the Endoplasmic Reticulum Require a Melanocyte-specific Factor

Abstract: Tyrosinase is a glycoprotein responsible for the synthesis of melanin in melanocytes. A large number of mutations have been identified in tyrosinase, with many leading to its misfolding, endoplasmic reticulum (ER) retention, and degradation. Here we describe the folding and maturation of human tyrosinase (TYR) using an in vitro translation system coupled with ER-derived microsomes or with semipermeabilized cells, as an intact ER source. TYR remained misfolded as determined by its sensitivity to trypsin digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…In support of this theory, previous studies show that mutant tyrosinase is misfolded (Francis et al, 2003;Halaban et al, 2000). Results of density gradient centrifugation indicated that control and mutant Tyr(C85S), and to some extent triglucosylated wild-type Tyr aggregated (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In support of this theory, previous studies show that mutant tyrosinase is misfolded (Francis et al, 2003;Halaban et al, 2000). Results of density gradient centrifugation indicated that control and mutant Tyr(C85S), and to some extent triglucosylated wild-type Tyr aggregated (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…As a consequence, cytosolic components including proteasomes can be washed away and subsequently added back in a controlled manner. Here, SP-membranes were isolated by centrifugation and resuspended in RRL optimized for the proper maturation of tyrosinase (Francis et al, 2003). Tyrosinase mRNA was then added to the mixture to translate 35 S-labeled tyrosinase selectively.…”
Section: Tyrosinase Is An Erad Substratementioning
confidence: 99%
See 2 more Smart Citations
“…The known melanosomal proteins are involved in melanogenesis as catalytic and/or structural components and include TYR, TYRP1, DCT, MART-1, and gp100 (60,70). Although the processing and sorting of those proteins are not completely understood, they are known to be synthesized and translocated into the ER and eventually into the Golgi where their post-translational processing and glycosylation take place (36,71). Following that processing, they seem to take distinct routes to traffic to melanosomes, with the majority of melanosomal proteins predominantly going to stage II melanosomes, although that distribution is disrupted in amelanotic melanoma cells.…”
Section: Discussionmentioning
confidence: 99%